Bibliometric Analysis of Global Research Output on Antimicrobial Resistance among Pneumonia Pathogens (2013-2023) - Nurgul Ablakimova; Gaziza A. Smagulova; Svetlana Rachina; Aigul Z. Mussina; Afshin Zare; Nadiar M. Mussin; Asset A. Kaliyev; Reza Shirazi; Nader Tanideh; Amin Tamadon (MDPI AG, 2023)
Antimicrobial resistance (AMR) is a pressing global concern, posing significant challenges to the effective treatment of infections, including pneumonia. This bibliometric analysis aims to investigate the research output on AMR among pneumonia pathogens from 2013 to 2023. Data were extracted from the Web of Science Core Collection (WOS-CC) using an inclusive search strategy. The analysis included 152 relevant studies published in 99 different sources, involving 988 authors and yielding an average of 16.33 citations per document over the past decade. The findings reveal a notable increase in research on AMR among pneumonia pathogens, indicating a growing awareness of this critical issue. Collaborative studies were prevalent, with the majority of authors engaging in joint research efforts. Bradford's Law identified twelve core journals that were instrumental in disseminating research in this field, with "Medicine" emerging as the most prolific journal. The USA and China emerged as the leading contributors, while Germany displayed a strong inclination towards collaborative research. Intermountain Medical Center, Saitama Medical University, and Udice-French Research Universities were the most productive institutions, and Yayan J. and Rasche K. were the top authors. Furthermore, the analysis identified commonly encountered microorganisms such as Acinetobacter baumanii and Klebsiella pneumoniae in the context of AMR. Time-based analysis of keywords highlighted the significance of terms like "community-acquired pneumonia" and "ventilator-associated pneumonia". Overall, this comprehensive study sheds light on the global research landscape of AMR among pneumonia pathogens. The insights gained from this analysis are essential for guiding future research priorities and collaborative efforts to combat AMR effectively and improve treatment outcomes for pneumonia and related infections. As the frequency of reports concerning resistance among pneumonia pathogens, notably A. baumannii and K. pneumoniae, continues to rise, there is an immediate requirement for pharmaceutical manufacturers and healthcare providers to respond proactively and ready themselves for the forthcoming implications of this matter. It also underscores the importance of knowledge dissemination and evidence-based interventions to address this growing public health challenge. However, the study acknowledges the limitations associated with using a single publication database and encourages the inclusion of data from other sources in future research.